Yeasts in food Beneficial and detrimental aspects - Boekhout, T. (Woodhead Publishing Ltd, 2003)
Yeasts play a crucial role in the sensory quality of a wide range of foods. This book provides a comprehensive review of the methods for their detection, identification and analysis as well as the role of yeasts in several food products including dairy products, meat, fruit, bread and beverages. Yeasts play a crucial role in the sensory quality of a wide range of foods. They can also be a major cause of food spoilage. Maximising their benefits whilst minimising their detrimental effects requires a thorough understanding of their complex characteristics and how these can best be manipulated by food processors. Yeasts in food begins by describing the enormous range of yeasts together with methods for detection, identification and analysis. It then discusses spoilage yeasts, methods of control and stress responses to food preservation techniques. Against this background, the bulk of the book looks at the role of yeasts in particular types of food. There are chapters on dairy products, meat, fruit, bread, soft drinks, alcoholic beverages, soy products, chocolate and coffee. Each chapter describes the diversity of yeasts associated with each type of food, their beneficial and detrimental effects on food quality, methods of analysis and quality control. With its distinguished editors and international team of over 30 contributors, Yeasts in food is a standard reference for the food industry in maximising the contribution of yeasts to food quality.
Keywords: Yeast.; Leavening agents.; Food contamination.; elektronické knihy; electronic books